Optimization of Integrated Nutrient Recommendations through Soil Test Crop Response Approach for Forage Oats (Avena sativa L.) in a Mollisol - Navneet Pareek and Poonam Gautam, Shalini Jhinkwan, Sobaran Singh* (Journal of the Indian Society of Soil Science, 2021)
A field experiment was conducted during the year 2018-19 to optimize integrated nutrient recommendations through soil test crop response approach for forage oats (Avena sativa L.) grown in a Mollisol of Uttarakhand. The experiment was conducted as per the technical programme and methodology of All India Coordinated Research Project (AICRP) on Soil Test Crop Response Correlation (STCR). Response of forage oats to selected combinations of three levels of farmyard manure (0, 5 and 10 t FYM ha-1), four levels of nitrogen (0, 40, 80 and 120 kg N ha-1), four levels of phosphorus (0, 30, 60 and 90 kg P2O5 ha-1) and four levels of potassium (0, 20, 40 and 60 kg K2O ha-1) at different soil fertility levels was studied. It was found that to produce one quintal forage yield, forage oats required 0.27 kg of N, 0.03 kg of P2O5 and 0.32 kg of K2O with FYM. The per cent contributions of N, P2O5 and K2O were 71.4, 33.7 and 59.9 from soil and 73.0, 7.51 and 90.4 from FYM, 89.6, 50.8 and 302.7 from chemical fertilizers and 102.4, 52.9 and 351.5 from conjoint use of chemical fertilizers with FYM. Using these data, fertilizer prescription equations were developed for adjusting fertilizer dose in forage oats for different range of soil test values and desired yield targets.